2020
DOI: 10.1155/2020/7308386
|View full text |Cite
|
Sign up to set email alerts
|

Notoginseng Leaf Triterpenes Ameliorates OGD/R-Induced Neuronal Injury via SIRT1/2/3-Foxo3a-MnSOD/PGC-1α Signaling Pathways Mediated by the NAMPT-NAD Pathway

Abstract: Background. Cerebral ischemic stroke (CIS) is a common cerebrovascular disease whose main risks include necrosis, apoptosis, and cerebral infarction. But few therapeutic advances and prominent drugs seem to be of value for ischemic stroke in the clinic yet. In the previous study, notoginseng leaf triterpenes (PNGL) from Panax notoginseng stem and leaf have been confirmed to have neuroprotective effects against mitochondrial damages caused by cerebral ischemia in vivo. However, the potential mechanisms of mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 75 publications
0
39
0
Order By: Relevance
“… 33 , 34 It had confirmed that NMN after systemic or local application would always be transformed to NAD+ and then demonstrated important regulation effects for kinds of diseases. 35 , 36 SIRT1 was one of the most confirmed NAD+ consuming enzyme, thus higher SIRT1 would be induced by NMN application in various disorders and biological progresses, including hepatocellular carcinoma, 37 adaptive thermogenesis 38 and osteogenesis. 39 In this current experiment, it was found that NMN-induced expression of SIRT1 could lead to a decreased level of IL-17a and this result might explain the biological mechanism of NMN application on DED, at least in part.…”
Section: Discussionmentioning
confidence: 99%
“… 33 , 34 It had confirmed that NMN after systemic or local application would always be transformed to NAD+ and then demonstrated important regulation effects for kinds of diseases. 35 , 36 SIRT1 was one of the most confirmed NAD+ consuming enzyme, thus higher SIRT1 would be induced by NMN application in various disorders and biological progresses, including hepatocellular carcinoma, 37 adaptive thermogenesis 38 and osteogenesis. 39 In this current experiment, it was found that NMN-induced expression of SIRT1 could lead to a decreased level of IL-17a and this result might explain the biological mechanism of NMN application on DED, at least in part.…”
Section: Discussionmentioning
confidence: 99%
“…Notoginseng leaf triterpenes (PNGL), which are the total saponins extracted from Panax notoginseng stems and leaves [ 100 , 101 ], are novel natural compounds that have recently been shown to activate Nampt gene expression [ 102 ]. PNGL has already been shown to possess antioxidative effects against a human neuroblastoma cell line [ 101 , 103 ].…”
Section: Possibility Of Nampt Activation By Small Moleculesmentioning
confidence: 99%
“…AMPK and SIRT1 have overlapping effects in the promotion of muscle mitochondrial biogenesis and oxidative stress. However, SIRT1 activation requires AMPK phosphorylation, further affecting PGC1α deacetylation [32,33]. Since the activation of AMPK/SIRT1 is closely related to biogenesis and the function of the muscle mitochondria, it is likely that AMPK/SIRT1 is a key target for the prevention and treatment of CRF and its related metabolic effects.…”
Section: Discussionmentioning
confidence: 99%